Are polymers glassier upon confinement?. Issue 31 (21st August 2015) - Spièce, Jean; Martínez-Tong, Daniel E.; Sferrazza, Michele; Nogales, Aurora; Napolitano, Simone
<x xml:space="preserve">Abstract</x> Confinement strongly improves the glass forming ability of thin films of PLLA.